A seção de obras raras da Biblioteca de Ciências Biomédicas da Fiocruz e a memória institucional da saúde pública no Brasil - Peruzzo, Tarcila (2013)
The main motivations for the development of this dissertation are: the lack of studies about the Seção de Obras Raras A. Overmeer of the Fundação Oswaldo Cruz (FIOCRUZ), the importance of this section for the memory of the institution as well as the contribution of personalities of the areas of medicine and librarianship to the formation and consolidation of this section. The objective of this work is to deepen the knowledge of the section characteristics, seeking a parallel between aspects of its creation and the outstanding initiatives in the area of public health which marked the end of the XIX and the beginning of the XX centuries in the country. One takes into account here the concepts institutional memory and of rare work , considering the complexity the latter and presenting the different perspectives taken by several authors. The importance of the historical and political dimensions of the rare work is also considered. A description is made of the circumstances of the creation of the FIOCRUZ s first library and of the role played by the doctor Oswaldo Cruz and the librarian Overmeer in the formation and the development of the collection. Present characteristics of the section and some of the highlights of its collection are also presented here. The main empirical focus of this study is the set of theses of the Faculty of Medicine of the UFRJ defended between the years of 1890 and 1925 - kept in the Section. These theses are here analyzed with respect to their formal and content aspects. The analysis of the formal aspects of the theses revealed that their pre-textual and pos-textual elements underwent a great variation in the period considered. The analysis of the theses content shows some subject variation in time. The sub-classes of the predominant subject public health is also a subject of analysis. The last step of the study consists of interviews with FIOCRUZ researches, seeking to find out their visions about the rare work and about the importance of the collection for their research. The interviews indicate that these researchers consider the Section the main responsible for the maintenance of the institutions memory and a rich source for their research. The combined evidence gathered in this study reveals the strong relationship between FIOCRUZs institutional memory and the Section characteristics.